2013
DOI: 10.1093/hmg/ddt114
|View full text |Cite
|
Sign up to set email alerts
|

ZEB2 zinc-finger missense mutations lead to hypomorphic alleles and a mild Mowat–Wilson syndrome

Abstract: Mowat-Wilson syndrome (MWS) is a severe intellectual disability (ID)-distinctive facial gestalt-multiple congenital anomaly syndrome, commonly associating microcephaly, epilepsy, corpus callosum agenesis, conotruncal heart defects, urogenital malformations and Hirschsprung disease (HSCR). MWS is caused by de novo heterozygous mutations in the ZEB2 gene. The majority of mutations lead to haplo-insufficiency through premature stop codons or large gene deletions. Only three missense mutations have been reported s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 29 publications
1
50
0
1
Order By: Relevance
“…Missense mutations of ZEB2 are a rare occurrence and were found in none of our cases. They have been described in the literature in association with mild presentations sharing some similarity with MWS, 31,32 although it is debatable whether most of these atypical cases should actually be classified as MWS. However, in addition to patients with missense mutations, there are a few cases also expected to behave differently than typical haploinsufficiency.…”
Section: Serious Infections Sepsismentioning
confidence: 99%
“…Missense mutations of ZEB2 are a rare occurrence and were found in none of our cases. They have been described in the literature in association with mild presentations sharing some similarity with MWS, 31,32 although it is debatable whether most of these atypical cases should actually be classified as MWS. However, in addition to patients with missense mutations, there are a few cases also expected to behave differently than typical haploinsufficiency.…”
Section: Serious Infections Sepsismentioning
confidence: 99%
“…Human mutations in one of the two alleles of ZEB2 cause Mowat-Wilson syndrome (MWS), which is characterised by a combination of defects with variable penetrance, including severe mental retardation, microcephaly, seizures, agenesis of the corpus callosum and poor hippocampal formation, as well as other nonbrain-related congenital defects like Hirschsprung disease and heart and craniofacial defects (Cacheux et al, 2001;Dastot-Le Moal et al, 2007;Garavelli et al, 2009;Ghoumid et al, 2013;Mowat et al, 2003;Saunders et al, 2009;Wakamatsu et al, 2001;Yamada et al, 2014;Zweier et al, 2005). The diverse range of defects in MWS reflect the multifunctional nature of ZEB2 during CNS and NCC development, as well as the wide range of MWS-causing ZEB2 mutations (>100 identified to date), the majority of which cause drastic C-terminal truncations of ZEB2.…”
Section: Zeb2 Mutation: the Causative Molecular Basis Of Mowatwilson mentioning
confidence: 99%
“…Prior reports suggest MWS typically leads to at least moderate and more often severe intellectual disability Adam et al, 2006;Garavelli and Cerruti-Mainardi, 2007;Evans et al, 2012]. However, recently, cases with a milder phenotype resulting from missense mutations and partial loss of ZEB2 function have been reported [Yoneda et al, 2002;Zweier et al, 2006;Ghoumid et al, 2013;Wenger et al, 2014]. Evans et al [2012] found that compared with an age and ID-matched comparison group, people with MWS showed a high rate of oral behaviors, including bruxism, an increased rate of repetitive behaviors, and an under-reaction to pain.…”
Section: Introductionmentioning
confidence: 99%